Social Сomfort in the Сontext of the Processes of Transformation in the Structure of Modern Russian Everyday Life - Z. M. Khachetsukov (Vestnik MGIMO-Universiteta)
This article analyzes the main approaches to the study of the social comfort, its manifestation in the space of everyday life within the modern Russian reality. Some approaches to the everyday life and the main approaches to the nature of social comfort and its dynamics are diseased.